Cardiovascular risk prevention and all‐cause mortality in primary care patients with an abdominal aortic aneurysm. Issue 12 (5th October 2016) - Bahia, S. S.; Vidal‐Diez, A.; Seshasai, S. R. K.; Shpitser, I.; Brownrigg, J. R.; Patterson, B. O.; Ray, K. K.; Holt, P. J.; Thompson, M. M.; Karthikesalingam, A.
Abstract : Background: Perioperative mortality is low for patients undergoing abdominal aortic aneurysm (AAA) repair, but long‐term survival remains poor. Although patients diagnosed with AAA have a significant burden of cardiovascular disease and associated risk factors, there is limited understanding of the contribution of cardiovascular risk management to long‐term survival. Methods: General practice records within The Health Improvement Network (THIN) were examined. Patients with a diagnosis of AAA and at least 1 year of registered medical history were identified from 2000 to 2012. Medical therapies for cardiovascular risk were classified as antiplatelet, statin or antihypertensive agents. Progression to death was investigated using the G‐computation formula with time‐dependent co‐variables to account for differences in exposure to cardiovascular risk‐modifying treatments and the confounding between exposure, co‐morbidities and death. Results: Some 12 485 patients had a recorded diagnosis of AAA. From 2000 to 2012, prescription of medications that modify cardiovascular risk increased: from 26·6 to 76·7 per cent for statins, from 56·5 to 73·9 per cent for antiplatelet agents and from 75·3 to 84·0 per cent for antihypertensive drugs. Adjusted Kaplan–Meier curves demonstrated a better 5‐year survival rate in patients receiving statins (68·4 versus 42·2 per cent), antiplatelet agents (63·6 versus 39·7 per cent) or antihypertensive agents (61·5 versus 39·1 per cent), compared with rates in patients not receiving each therapy. Conclusion: Appropriate risk factor modification could significantly reduce long‐term mortality in patients with AAA. In the UK, up to 30 per cent of patients are not currently receiving these medications. Abstract : Statins and aspirin save lives